Molecular Characterization of German Acinetobacter baumannii Isolates and Multilocus Sequence Typing (MLST) Analysis Based on WGS Reveals Novel STs - Gamal Wareth; Jörg Linde; Philipp Hammer; Wolf D. Splettstoesser; Mathias W. Pletz; Heinrich Neubauer; Lisa D. Sprague (Pathogens, 2021)
Acinetobacter baumannii (A. baumannii) is a major cause of severe nosocomial infections worldwide. The emergence of infections associated with A. baumannii poses a significant health risk in Germany. A. baumannii is part of the ACB complex and is difficult to distinguish from other species phenotypically, necessitating its reliable identification. The current study analyzed 89 A. baumannii strains from human and non-human origins by matrix-assisted laser desorption/ionization (MALDI–TOF) and PCR detection of intrinsic blaOXA-51-like carbapenemase, blaOXA-23-like, blaOXA-24-like, blaOXA-58-like, and ISAba 1 genes. Whole-genome sequencing (WGS) was applied for species confirmation and strain type determination. Combining the molecular detection of the intrinsic blaOXA-51-like carbapenemase gene together with MALDI–TOF with a score value of >2.300 proved to be a suitable tool for A. baumannii identification. WGS data for all of the sequenced strains confirmed the identity of all A. baumannii strains. The Pasteur scheme successfully assigned 79.7% of the strains into distinct STs, while the Oxford scheme succeeded in allocating only 42.7% of isolates. Multilocus sequence typing (MLST) analysis based on the Pasteur scheme identified 16 STs. ST/241 was the most prevalent in samples from non-human origin, whereas ST/2 was predominant in human samples. Furthermore, eight isolates of non-human origin were allocated to seven new STs (ST/1410, ST/1414, ST/1416, ST/1417, ST/1418, ST/1419, and ST/1421). Ten isolates from non-human origin could not be typed since new alleles were observed in the loci Pas_cpn60, Pas_rpoB, and Pas_gltA. MLST analysis based on the Pasteur scheme was more appropriate than the Oxford scheme for the current group of A. baumannii.